Aventura Científica: Video Games as a Tool for Teaching Science in Elementary Education - Mendes, Rodrigo Jeremias; Sousa, Pedro Moises de (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
This paper details the development process of a digital educational game named "Aventura Científica". Utilizing the Unity graphics engine and following agile methodologies emphasizing incremental and iterative application development, the game aims to teach general science topics in a captivating manner, exploring the imagination and playful side of elementary school children. "Aventura Científica" was tested in two public educational institutions with students in the 5th and 6th grades, aged 10 to 12 years, receiving positive feedback from both educators and students. The collected results suggest that the game can serve as a supportive tool in the teaching process.